SIKAP APARATUR SIPIL NEGARA DI LINGKUNGAN DITJEN PAJAK TERHADAP PELAKU PENUNGGAK PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR UTARA (TELAAH HUKUM ISLAM) - Esar, Andi; Samin, Sabri (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
This article describes how the existence of state civil servants within the Directorate General of Taxes against perpetrators in arrears at the North Makassar Primary Tax Service Office. The main problems in this research are: 1) How is the existence of ASN against the perpetrators of tax arrears at the North Makassar Pratama Tax Office? 2) How do the state civil servants at the North Makassar Primary Tax Office handle tax arrears? This research is classified as a type of qualitative field research and uses a normative juridical approach. This research is carried out through a series of activities such as observation, interviews, and document review. The results show that the existence of state civil servants in dealing with tax arrears in KKP Pratama Makassar Utara has effective in extracting tax potential and efficiency in collecting tax. In its efforts, ASN Pajak itself has determined policy in the event of a violation of tax arrears in its collection, it must be resolved administratively. The Directorate General of Taxes also took the initiative by striving to provide educational media and information delivery that can reach all people and taxpayers appropriately and easily, so that the public and taxpayers can access information through these media.